Phenol Biodegradation and Catechol 2,3-Dioxygenase Gene Sequencing of Bacillus cereus IrC2 isolated from Rungkut Indonesia - Candra Yulius Tahya; Wahyu Irawati; Friska Juliana Purba (Jurnal Kimia Terapan Indonesia, 2019)
Phenol is toxic organic compounds that harmful to humans, mammals, and disrupt the aquatic environment, especially higher-organisms in fresh-water environment. The biodegradation method using bacteria to degrade hazardous chemical and detoxify wastewater is an effective and efficient method. Bacillus cereus IrC2 isolated from sludge in an industrial wastewater treatment plant in Rungkut – East Java, Indonesia has been examined for the ability to degrade phenols in minimal salt medium. Bacillus cereus IrC2 is Gram-positive bacterium. This bacterium is motile, rod-shaped and its nucleotides sequence of 16S rRNA gene has been sequenced and can be accessed in GenBank with accession number MK511840. Bacillus cereus IrC2 is capable to use phenol up to 400 ppm as the sole carbon source to grow for 48 hours incubation. Phenol degrades 96% from initial concentration. Degradation of phenol was calculated by colorimetric method using 4-aminoantipyrine reagent and confirmed by GC MS analysis. The aerobic degradation of phenol pathways consists of three steps; in the first step, two hydroxyl groups are inserted into aromatic ring and catalyzed by mono or dioxygenase to produce dihydroxy aromatic compounds which are mostly catechols. Catechol enters the next step of aromatic ring cleavage catalyzed by catechol 1,2-dioxygenase and/or catechol 2,3- dioxygenase. The catechol 2,3-dioxygenase gene of Bacillus cereus IrC2 has been amplified by PCR and cloned into pTA2 vector. The cloned plasmid (pTA2-catE) was transformed into E. coli DH5α and selected blue-white colonies. The insert sequence was determined by Sanger deoxy sequencing method. The catechol 2,3-dioxygenase gene nucleotides sequence of Bacillus cereus IrC2 was submitted nto GenBank with accession number MK561609.